Correlation Analysis Of Menstrual Cycle On Cardiorespiratory Capacity And Anaerobic Performance In Female Athletes - Afidah Sutralia; Wajendra kenny willa tikat; Liana Azahra; Muhammad Arief Setiawan; A. Ine Aprilia Damai; Aprillia Wulan Utari (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
The menstrual cycle is a physiological factor thought to influence the physical performance of female athletes through periodic hormonal changes. Fluctuations in estrogen and progesterone levels during the menstrual cycle have the potential to impact athletes' cardiorespiratory capacity and anaerobic performance. This study aimed to analyze the relationship between the menstrual cycle and cardiorespiratory capacity and anaerobic performance in female athletes. The study used a quantitative approach with a correlational design. observational and repeated methods The study sample consisted of 30 active female athletes aged 18–25 years who were selected using a purposive sampling technique. Cardiorespiratory capacity measurements were conducted using the Multistage Fitness Test (MFT) to obtain VO₂max values , while anaerobic performance was measured using Running-based Anaerobic Sprint Test (RAST). Data were analyzed using descriptive analysis, normality test Shapiro-Wilk , homogeneity test, Pearson Product correlation test Moment , and Repeated Measures ANOVA. The results showed that the follicular phase had the highest VO₂max and maximum power values compared to the menstrual phase and the luteal phase . The correlation test results showed a significant relationship between the menstrual cycle and VO₂max (r=0.642; p=0.001), maximum power (r=0.587; p=0.003), and fatigue. index (r=-0.511; p=0.007). In addition, the results of Repeated ANOVA measures showed significant differences in cardiorespiratory capacity and anaerobic performance between menstrual phases (p<0.05). It was concluded that the menstrual cycle significantly influences cardiorespiratory capacity and anaerobic performance in female athletes, and therefore needs to be considered when developing high-performance sports training programs.